PENGARUH PERUBAHAN PENGGUNAAN LAHAN TERHADAP PERUBAHAN SUHU DI KECAMATAN GUNUNG PUTRI KABUPATEN BOGOR PADA TAHUN 2010-2020 - Ardiansyah, Andri Noor; Firmansyah, Firmansyah; Nuraeni, Neng Sri (Jurnal Konservasi dan Rekayasa Lingkungan, 2024)
Study This aim For know change use land Subdistrict Mountain Daughter Year 2010-2020, change temperature Subdistrict Mountain Daughter Year 2010-2020 and influence change use land to change temperature in the District Mountain Daughter 2010-2020 year . Approach research used _ on study This is is approach quantitative descriptive with helped use system information geographical And sensing far . Materials used _ that is  image landsat 7 year 2010 and image landsat 8 year 2020. Population on study This that is Subdistrict Mountain Daughter Bogor Regency . Data analysis used that is analysis simple linear regression . Results study This showing that there is influence change use land to change temperature in the District Mountain Daughter 2010-2020 year . As for change use land from 2010-2020 year biggest happen on land agriculture Where experience subtraction of 54.14% or area (1007.889 Ha), land awakened experience increase wide by 22.97% or area (688.197 Ha), vegetation experience increase of 29.24 % (317.896 Ha), the body of water experienced increase of 4.90 % (3.322 Ha) and land open experience an increase of 1.23% or area (1,693 Ha). Next change temperature from In 2010-2020, the minimum temperature was at in 2010 by 20ºC and in 2020 it is 22ºC meanwhile temperature maximum on in 2010 by 30ºC and in 2020 it was 32ºC. furthermore results test normality got of ) of 0.200 more from α (0.05), then done simple linear regression And generated value 828,773, next done t test and test f and got mark significance (sig) of 0.004 <0.05 and the last done test coefficient determination And got R square value of 0.685 then from That can concluded that influence change use land to change temperature by 68.5% meanwhile the remaining 31.5% were affected by variable outside study this.